An improved chaotic image encryption algorithm - Al-Khasawneh, Mahmoud Ahmad; Shamsuddin, Siti Mariyam; M.Kamrul Hasan, Shafaatunnur; Ibrahim, Adamu Abubakar (Institute of Electrical and Electronics Engineers Inc., 2018)
Chaotic-based image encryption algorithms are countless in number. Encryption techniques based on Chaos are among the most effectual algorithms for encryption of data image. In past works, chaos-based cryptosystems applied the chaotic dynamical system with the linkage to the harmonization of two chaotic systems and controls. Good performances have resulted but there were several downsides pertaining to the single rule usage by each, impacting security, privacy and dependability of the techniques mentioned. Serious problems were also documented in their usage in satellite imagery. As a possible solution, a novel chaos-based symmetric method of key cryptosystem is proposed in this paper. This method employs external secret key that Logistic, Henon and Gauss iterated maps have previously expanded. For creating the secret key matrix for image encryption, these maps are merged. Here, simple logical XOR and multiple key generation processes were applied. Assessment to the method is performed on the satellite images dataset, and security is evaluated through the experimental analysis. As evidenced, the chaos-based satellite image cryptosystem demonstrates appropriateness for satellite image encryption and decryption in the preservation of security and dependability of the storage and transmission process.